Performance anxiety: How to play reliable and rational tennis by reducing mental pressure - Esposito, G.; Ceruso, R.; D'Elia, F.; D'Isanto, T. (Journal of Human Sport & Exercise, 2020)
Almost all tennis players, from beginners to professionals, would be able to perform better, and therefore be more performing, if only they were able to lower the level of mental pressure during a game. When it increases dramatically, it is the cause of technical, tactical errors and unorthodox attitudes, as well as significantly reducing confidence in one's own means. The purpose of this study is to identify the most appropriate tactical and technical behaviours to adopt in the sport in question to play a more reliable tennis in the various game situations. The method is empirical research for the analysis of technical and tactical. The method is empirical research for the analysis of technical and tactical foundations, with a subsequent comparative method between grids of indicators, descriptors and weights that classifies the behaviours to be adopted. The data are useful to provide a practical guide to follow in order to approach this sport correctly, especially for children, reducing the responsibilities incurred by them and eliminating the expectations of parents and trainers about them. The results are useful for any reflections and focus on the reproducibility of the topic investigated to other sports activities through an educational and training action.